Stalin's great science the times and adventures of Soviet physicists - Kozhevnikov, A. B. (History of modern physical sciences ;, 2004)
World-class science and technology developed in the Soviet Union during Stalin's dictatorial rule under conditions of political violence, lack of international contacts, and severe restrictions on the freedom of information. This book investigates this paradoxical success by following the lives and work of Soviet scientists - including Nobel Prize-winning physicists Kapitza, Landau, and others - throughout the turmoil of wars, revolutions, and repression that characterized the first half of Russia's twentieth century.